2013
DOI: 10.1007/s11011-013-9401-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting oncogenic ALK and MET: a promising therapeutic strategy for glioblastoma

Abstract: Glioblastoma is the most common aggressive, highly glycolytic, and lethal brain tumor. In fact, it is among the most commonly diagnosed lethal malignancies, with thousands of new cases reported in the United States each year. Glioblastoma's lethality is derived from a number of factors including highly active pro-mitotic and pro-metastatic pathways. Two factors increasingly associated with the intracellular signaling and transcriptional machinery required for such changes are anaplastic lymphoma kinase (ALK) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…The impressive efficacy of targeting f ALK in NSCLC and ALCL raised interest in ALK alterations in other cancer types. Several studies have shown the efficacy of anti‐ALK therapies in a wide variety of malignancies , but these studies are small‐scale and generally limited to individual case reports or case studies. In addition, many of these publications targeted ALK alterations that were not classic gene fusions, and included both ALK gene amplifications and ALK ‐activating base substitutions .…”
Section: Introductionmentioning
confidence: 99%
“…The impressive efficacy of targeting f ALK in NSCLC and ALCL raised interest in ALK alterations in other cancer types. Several studies have shown the efficacy of anti‐ALK therapies in a wide variety of malignancies , but these studies are small‐scale and generally limited to individual case reports or case studies. In addition, many of these publications targeted ALK alterations that were not classic gene fusions, and included both ALK gene amplifications and ALK ‐activating base substitutions .…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, CyclinB1 is a known regulator of the cell cycle (40), Alk promotes growth and anti-apoptotic pathways (41), while ezrin, radixin, moesin (ERM), and merlin comprise the ERM family of proteins, which link membrane proteins to the actin cytoskeleton (34). Notably, Alk is reportedly overexpressed in GBM tumors (41), ezrin and its functions are associated with tumor cell migration and tumor invasion in GBM and other cancers (42), and with increasing malignancy of astrocytic tumors (43), while merlin causes contact-dependent growth inhibition, decreased proliferation, increased apoptosis, and tumor growth inhibition (44,45). We particularly note the pattern of a seemingly inverse correlation between the expression levels of pS10merlin and the pro-oncogenic pY478ezrin (46) in response to 15α-MP treatment, highlighting the importance of the two genes in the anti-tumor mechanisms of the natural product.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we show that CMET overexpression and CMET amplification are commonly found in NSCLC BM and may thus represent a promising therapeutic target. Specific inhibitors of the HGF/CMET axis that may penetrate the blood–brain/blood–tumour barrier are being developed for primary brain tumours such as glioblastoma and may also be rational experimental therapeutics for selected BM patients …”
Section: Discussionmentioning
confidence: 99%